Propagating and banking genetically diverse human sapovirus strains using a human duodenal cell line: investigating antigenic differences between strains - Oka, Tomoichiro; Li, Tian-Cheng; Yonemitsu, Kenzo; Ami, Yasushi; Suzaki, Yuriko; Kataoka, Michiyo; Doan, Yen Hai; Okemoto-Nakamura, Yuko; Kobayashi, Takayuki; Saito, Hiroyuki; Mita, Tetsuo; Tokuoka, Eisuke; et al. (Journal of Virology, 2024)
The control of human sapovirus, which causes acute gastroenteritis in individuals of all ages, is challenging because of its association with outbreaks similar to those caused by human norovirus. The establishment of conditions for efficient viral propagation of various viral strains is essential for understanding the infection mechanism and identifying potential control methods. In this study, two critical factors for human sapovirus propagation in a conventional human duodenal cell line were identified, and 15 strains of different genotypes that differed at the genetic and antigenic levels were isolated and used to prepare virus stocks. The preparation of virus stocks has not been successful for noroviruses, which belong to the same family as sapoviruses. Securing virus stocks of multiple human sapovirus strains represents a significant advance toward establishing a reliable experimental system that does not depend on limited virus-positive fecal material.